Maintenance Model and Bali Cattle Density in the Development Center of South Konawe Regency, Southeast Sulawesi - Gerhana; W. Rindayati; D. S. Priyarsono (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2025)
The maintenance model and cattle density of Bali cattle in a central development region can influence the region’s capacity to accommodate the developed Bali cattle. Therefore, regions capable of managing good maintenance models and cattle density management are crucial to enhancing the competitiveness of Bali cattle. The purpose of this research is to analyze the cattle-raising model and the density of Bali cattle in the development center of South Konawe Regency, Southeast Sulawesi. The research was conducted from June to August 2024. The research location was determined using purposive sampling in South Konawe Regency, focusing on four priority districts for Bali cattle development: Baito, Palangga, Buke, and Tinanggea, with 240 respondents being Bali cattle farmers. The research results indicate that based on the economic density parameter, the value is 107.60 ST (high), farming density is 0.19 ST (moderate), and regional density is 8.19 ST (low). According to the combinations of livestock density, thefarming-region combination has a value of 4, while the economy-farming combination and economyregion combination both have a value of 3. In terms of the rearing model, 71% of Bali cattle are raised using a semi-intensive system, while 29% are raised intensively. Additionally, the combined rearing pattern of breeding and fattening accounts for 64%, with fattening alone at 36%. Thus, the livestock density in South Konawe Regency indicates that the economic density still has potential for developing Bali cattle. The farming density is still very capable of accommodating more Bali cattle than currently present, and the regional density offers significant opportunities for Bali cattle development. The areas of distribution and development exist within the farming-region combination, while development areas are found within the economy-farming and economy-region combinations. The predominant rearing model is semi-intensive, while the breeding model is combined with fattening.